Infected Leiomyoma: A Case Report and Review of Literatures - Atthapon Jaishuen; Suwanich Theresakvitchaya (Siriraj Medical Journal, 2006)
A 57-year-old, single Thai woman presented with a sudden onset of severe pain in the right lower quadrant of the abdomen. The patient had intermittent abdominal pain for five months. Previous pelvic examination and ultrasonography demonstrated a right adnexal mass compatible with right ovarian tumor or subserous myoma. An exploratory laparotomy revealed a ruptured infected leiomyoma. Total abdominal hysterectomy and bilateral salpingo-ophorectomy were performed.Â Antibiotics therapy was continued post operatively until clinical improved. Although the infected leiomyoma is uncommon, theÂ diagnosis should be considered in septic patients with history of leiomyoma, especially in those who had the risk of uterine infection.